Effectiveness of Hand Line and Kite Line Fishing Gear in Tuna (Thunnus sp.) Fisheries in Makbon Waters, Sorong Regency - Jamaluddin Fitra Dasi; Roger R. Tabalessy; Melisa Masengi (INTEGRATED OF FISHERIES SCIENCE, 2025)
Large pelagic tuna (Thunnus sp.) is a high-value fishery resource that significantly contributes to Indonesia’s fishing industry. This study evaluates the effectiveness of two primary fishing gear types—hand line and kite line—in tuna fisheries in Makbon waters, Sorong Regency, West Papua. Field research was conducted using a survey approach with direct observations on 14 fishing trips. Results demonstrated that hand line yielded 52 tuna individuals (65.8% effectiveness), while kite line yielded 27 individuals (34.2% effectiveness). This difference is significant and influenced by technical factors including operational depth, gear selectivity, and target fish behavior. Hand line effectively reaches optimal tuna depths and exhibits higher selectivity for catching marketable-sized individuals. This research emphasizes the importance of appropriate gear selection in enhancing catch productivity while maintaining tuna resource sustainability. Policy recommendations include regulating hand line use as the primary fishing gear and implementing monitoring systems to ensure the capture of adult fish